Synthesis, Characterization and Pharmacological Evaluation of 1-(2-Chloro-6-Fluorophenyl)-5-Methylindolin-2-One: A New Anti-Inflammatory Compound with Reduced Gastric Ulceration Properties - dos Santos, Jean Leandro [UNESP]; Chelucci, Rafael [UNESP]; Chiquetto, Richard [UNESP]; Chin, Chung Man [UNESP]; Campos, Michel Leandro [UNESP]; Peccinini, Rosangela Goncalves [UNESP] (Mdpi Ag, 2010)
The new compound 1-(2-chloro-6-fluorophenyl)-5-methylindolin-2-one (1), designed using the prodrug approach, was easily obtained in 85% yield and characterized by nuclear magnetic resonance, elemental analysis, mass spectrometry and infrared spectroscopy. The lactam 1 showed anti-inflammatory and analgesic activity comparable to that of the COX-2 inhibitor lumiracoxib, without gastro-ulceration effects. Stability studies demonstrated that the lactam function was stable and did not hydrolyze in pH 1.2 or 7.4. Furthermore, using a thioglycollate-induced peritonitis model, compound 1 was shown to inhibit cell migration by 50.4%, while lumiracoxib inhibited it by 18%. This compound represents a new non-ulcerogenic prototype for the treatment of chronic inflammatory diseases.
Keywords: pro-drug; lactam; lumiracoxib; anti-inflammatory